(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: As the best management of subclinical hypothyroidism is controversial, we aimed to assess variations in treatment strategies depending on different Swiss regions, physician and patient characteristics. METHODS: We performed a case-based survey among general practitioners (GPs) in different Swiss regions, which consisted of eight hypothetical cases presenting a female patient with subclinical hypothyroidism and nonspecific complaints differing by age, vitality status and thyroid-stimulating hormone (TSH) concentration. RESULTS: A total of 262 GPs participated in the survey. There was considerable variation in the levothyroxine starting dose chosen by GPs, ranging from 25 µg to 100 µg. Across the Swiss regions, GPs in the Bern region were significantly more inclined to treat, with a higher probability of initiating treatment (60%, p = 0.01) and higher mean starting doses (45 µg, p <0.01) compared with the French-speaking region (44%, 36 µg); the Zurich region had intermediate values (52%, 39 µg). We found no association between treatment rate and other physician characteristics. GPs were more reluctant to initiate treatment in 85-year-old than in 70-year-old women (odds ratio [OR] 0.77, 95% confidence interval [CI] 0.63–0.94), and more likely to treat women with a TSH of 15 mU/l than those with a TSH of 6mU/l (OR 8.71, 95% CI 6.21–12.20). CONCLUSIONS: There are strong variations in treatment strategies for elderly patients with subclinical hypothyroidism across different Swiss regions, including use of higher starting doses than the recommended 25 µg in the Swiss guidelines, which recommend a starting dose of 25 µg. These variations likely reflect the current uncertainty about the benefits of treatment, which arise from the current lack of evidence from adequately powered clinical trials.